A Proposal of Chatbot for Malayalam - Sandhini, S; Binu, R; Rajeev, R.R; Reshma, M.M (International Journal of Computer Sciences and Engineering, 2018)
A chatbot is a conversational agent which interacts with humans via natural languages. Text as well as speech, is used as the input to these systems. We propose a Malayalam chatbot based on a natural language processing with machine learning techniques library on a language-independent platform. The chatbot is a retrieval based model which can converses in Malayalam. Malayalam is a Dravidian language talked over the Indian state of Kerala. Machine learning as well as NLP (Natural Language Processing) approaches are used to analyze user queries and generate responses. We experiment an AIML (Artificial Intelligence Markup Language) based chatbot and a machine learning based chatbot. Among the two bots, the machine learning chatbot performs better. We developed a domain-specific chatbot. It is a commercial product, so we can apply this to any domain.